(untitled) (Medical Forum Monthly, 2026)
Objective: To evaluate transfusion and chelation status among thalassemia patients, determine the prevalence of hyperglycemia, and assess whether adherence to chelation therapy is associated with differences in hyperglycemia severity. Study Design: Descriptive cross-sectional study Place and Duration of Study: This study was conducted at the Department of Pathology (Hematology) in collaboration with the Department of Pediatrics, Pakistan Railways Hospital (PRH), and the Thalassemia Center, Rawalpindi from September 2023 to September 2024. Methods: A total of 137 patients with thalassemia major were assessed. Patients were categorized into three management groups: well transfused and adequately chelated (12.4%), well transfused but inadequately chelated (29.9%), and irregularly transfused with inadequate chelation (57.7%). Glycemic status was classified as normal, impaired glucose regulation, or diabetes mellitus. Results: Among the 137 patients, 55.5% had normal glucose levels, 32.8% had impaired glucose regulation, and 11.7% were diabetic. Diabetes showed a significant association with irregular transfusion and inadequate chelation (p < 0.001). Of the diabetic patients, 78.5% were irregularly transfused and inadequately chelated, while 21.5% were well transfused but inadequately chelated. Importantly, none of the well transfused and adequately chelated patients were diabetic. Conclusion: Effective transfusion schedules combined with adequate chelation therapy appear protective against the development of diabetes in thalassemia major. Poor adherence to transfusion and chelation regimens is strongly linked with hyperglycemia and diabetes, underscoring the need for strengthened patient education, monitoring, and early intervention strategies to prevent iron-related endocrine complications.